Melancholy or mahjong? diversity, frequency, type, and rural-urban divide of social participation and depression in middle- and old-aged Chinese: a fixed-effects analysis - Wang, Ruoxi; Chen, Zhuo; Zhou, Yongjie; Shen, Lining; Zhang, Zhiguo; Wu, Xiang (2019)
The potential benefit of social participation (SP) to one's mental health has been widely acknowledged. Nevertheless, the specific type and amount of SP that is associated with improved depressive symptoms in middle- and old-aged Chinese awaits further investigation. This study aimed to understand the patterns of depression and SP by comparing urban vs rural China, and according to which, measure the associations between changes in SP and that in depressive symptoms. A total of 10,988 community residents aged 45 years and above were selected from wave 1 (2011), wave 2 (2013), and wave 4 (2015) of the China Health and Retirement Longitudinal Study (CHARLS), a nationally representative survey. The fixed-effects analysis was used to explore the association between the changes in diversity, frequency, and type of SP and the changes in depressive symptoms. The results indicated that rural respondents suffered from a significantly higher risk of depression and took less SP than their urban counterparts. Transitioning from no SP to 1 or more types of SP or to a once a week or higher frequency was associated with a decline in depressive symptoms. For urban respondents, playing mah-jong or cards and joining sports or social clubs predicted a decline in depressive symptoms. For rural residents, interacting with friends regularly was associated with fewer depressive symptoms. In conclusion, more diverse and higher frequency of SP was associated with better mental health, while the social significance of SP varied across different types of SP and between rural and urban areas. © 2019 Elsevier Ltd